Efektivitas Teknik Jigsaw untuk Meningkatkan Kemampuan Siswa dalam Menulis Teks Narasi - Suryani Suryani; Putri Dini Meutia; Ema Dauyah; Dawani Dawani (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The research was conducted in order to know the effectiveness of using Jigsaw technique in improving students’ ability in writing narrative text. The aims of this research were to what extent the effectiveness of Jigsaw technique in improving students’ ability in writing narrative and to find out the students’ responses about the application of Jigsaw technique in the learning process. This research used Pre-Experimental research and used one group pretest-posttest. Test and questionnaire were utilized as the research instruments. The result of this research indicated that the mean score of the students in pretest before they were taught using the Jigsaw technique was 40,5. While the mean score of the students in writing narrative text after they were taught using the Jigsaw technique was 69,75. The t-score was 15,41 meanwhile, t-table with significant level 5% was 2,093. It meant that the t-score was higher than the t-table. From this result shown, Ha was accepted. It can be concluded that using the Jigsaw technique is effective to improve the students’ ability in writing narrative text.